Bullous pemphigoid and mucous membrane pemphigoid humoral responses differ in reactivity towards BP180 midportion and BP230 - Mariotti, Feliciana; Pira, Anna; De Luca, Naomi; Giampetruzzi, Anna Rita; Russo, Filomena; Cerri, Amilcare; Gasparini, Giulia; Cozzani, Emanuele; Marzano, Angelo V.; Antiga, Emiliano; Caproni, Marzia; Quaglino, Pietro; et al. (Frontiers in Immunology, 2024)
BackgroundBullous pemphigoid (BP) and mucous membrane pemphigoid (MMP) are rare autoimmune blistering disorders characterized by autoantibodies (autoAbs) targeting dermo-epidermal junction components such as BP180 and BP230. The differential diagnosis, based on both the time of appearance and the extension of cutaneous and/or mucosal lesions, is crucial to distinguish these diseases for improving therapy outcomes and delineating the correct prognosis; however, in some cases, it can be challenging. In addition, negative results obtained by commercially available enzyme-linked immunosorbent assays (ELISAs) with BP and MMP sera, especially from patients with ocular involvement, often delay diagnosis and treatment, leading to a greater risk of poor outcomes.ObjectivesOur aim was to find potentially different reactivity profiles in BP and MMP and improve available approaches for diagnosis with focus on ocular MMP.MethodsTwo cohorts of 90 BP and 90 MMP, recruited from different Italian clinical centers, were characterized also employing a novel ELISA based on the BP180 extracellular domain (ECD-BP180).ResultsImmunoglobulin G (IgG) reactivity to BP180 and BP230 in MMP sera was significantly reduced in comparison with BP, mostly affecting BP230 and E-1080 (53% and 36% in BP vs. 11% and 3% in MMP, respectively, p < 0.0001). The combined sensitivity of BP180-NC16A and ECD-BP180 ELISAs was greater compared to BP180-NC16A and BP230 ELISAs both in BP (97% and 92%, respectively) and in MMP (42% and 31%, respectively). The present study shows that MMP patients with ocular involvement rarely reacted to BP180 by IgG in contrast with patients with oral and/or cutaneous involvement (p = 0.0245 and p = 0.0377, respectively), suggesting that an oral and/or cutaneous MMP positive to BP180 hardly evolves to ocular MMP. Of note, one-third of ocular MMP showed immunoglobulin A (IgA) reactivity to ECD-BP180 by immunoblotting.ConclusionsThe present study provides several hints to perform a correct and timely diagnosis in BP and MMP, which is crucial for improving therapy outcomes and delineating the correct prognosis.